Studi Empiris tentang Kontribusi Harga, Varian Produk, dan Kemasan terhadap Pembentukan Minat Beli Produk Sabun Mandi Batang (Studi Kasus terhadap Pekerja Rantau di Kota Surabaya) - Didit Darmawan; Samsul Arifin (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2021)
Every brand owner must understand the desires of his consumers from the products he offers through the exchange process. Bar soap products still have regular consumers and the market potential is still growing. Packaging is one form of physical communication that the company makes to potential customers as well as a product attraction. Packaging has the potential to attract consumers to buy products because of the tendency of consumers to be easily attracted by their physical attention. In addition, prices can attract consumers' attention if they are aimed at the right target market. To strengthen repurchase interest, brand owners use product variants so that consumers have a wide choice of brands. This study aims to determine the effect of price, product variants and packaging on product purchasing decisions. The population in this study were users of bar soap in the city of Surabaya. Samples were taken from a group of boarding house workers and bar soap users who chose the brand and used it. The number of samples was 87 people who were determined based on the purposive sampling method. The analysis tool is multiple linear regression analysis. The results showed that all independent variables had a significant effect on the dependent variable. Likewise, the simultaneous influence on the dependent variable. The variable that has a dominant effect is indicated by the price variable.